Stability-Indicating Liquid Chromatographic Methods with Photodiode Array Detection and Light Scattering Detection for Simultaneous Determination of Candesartan and Hydrochlorothiazide. (11th December 2017) - de Diego, Marta; Godoy, Ricardo; Mennickent, Sigrid; Vergara, Carola; Miranda, Daniel; Navarro, Pía
Abstract: Development, validation and comparison of two stability-indicating LC methods, one with photodiode array detector (DAD) and the other with evaporative light scattering detector (ELSD), were performed for simultaneous determination of candesartan cilexetil (CANC) and hydrochlorothiazide (HCTZ), in pharmaceutical samples. A RP-18 column (125 mm × 4 mm, 5 μm) was used for separation of CANC, HCTZ and its major degradation products, using acetonitrile and phosphate buffer (pH 6.0) for DAD method and acetonitrile and water with acetic acid and triethylamine (pH 4.1) for ELSD method, as mobile phase in a gradient mode. The response with ELSD was fitted to a power function and the DAD response by a linear model over a range of 32–160 μg/mL for CANC and 25–125 μg/mL for HCTZ. The precision and accuracy of the methods were similar, with RSD below 3.0% and recovery between 98.1% and 103.9%. The drugs were subjected to stress conditions of hydrolysis, oxidation, photolysis, humidity and temperature. The degradation products were satisfactory separated from the main peaks and from each other. Both drugs mainly degrade by hydrolysis, showing the formation of one degradation product for HCTZ and two for CANC; its identification was conducted by LC/MS/MS. The methods were successfully applied to the analysis of CANC and HCTZ in combined commercial tablets. The performance of DAD and ELSD methods are comparable, therefore both methods are suitable for stability study and determination of CANC and HCTZ in pharmaceutical samples.